Development of Interactive Multimedia Pacelathon to Strengthen Javanese Language Literacy Skills - Ananda Putri, Jihan Herawati; Suttrisno; Nurul Mahruzah Yulia (Journal of Practice Learning and Educational Development, 2025)
This research was conducted in response to the low literacy skills in reading and writing the Javanese language among elementary school students, particularly in the use of unggah-ungguh basa (levels of politeness in Javanese speech). Many students at MI Islamiyah Ngrejeng still struggle to use krama (formal Javanese) in daily communication. The aim of this study is to develop an interactive multimedia product called Pacelathon and to analyze its development process, results, and effectiveness in strengthening students’ Javanese literacy. This study employed the Research and Development (R&D) approach using the ADDIE model, which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The multimedia developed integrates animated videos, Wordwall quizzes, and audio narration in Javanese accents. Expert validation results showed a high level of feasibility: 92.5% from media and language experts and 90% from subject matter experts. The effectiveness test revealed an increase in students’ average scores from 79% (pre-test) to 86% (post-test), with an N-Gain score of 0.33, which falls into the moderate category. These findings indicate that the Pacelathon interactive multimedia is both feasible and moderately effective in improving students’ literacy in the Javanese language, and it can serve as a meaningful learning tool to preserve local culture through education.